(untitled) (Euro-Latin American Journal of Administrative Law, 2014)
A specialty of the Federal State itself is referred to a necessary balance between its component entities. This delicate attribute has been shown to be difficult to access on federalism as a whole and in Brazil it has propitiated the creation of regions of development among the Member States and metropolitan areas between Municipalities, without compromising the division of competences provided by the Constitution, i.e., the autonomy necessary for existence as partial federal entity. The Brazilian Fundamental law strengthened the Union’s capacity to regulate most of the performances of the public authorities, which led to the emptying of the decision-making power of the municipality and to distancing from its local interest, turning the Municipality into a simple executor of the policies determined by federal government.